Comparative Metabolomics and Lipidomics of Four Juvenoids Application to Scylla paramamosain Hepatopancreas: Implications of Lipid Metabolism During Ovarian Maturation - Fu, Yin; Zhang, Fengying; Ma, Chunyan; Wang, Wei; Liu, Zhiqiang; Chen, Wei; Zhao, Ming; Ma, Lingbo (Frontiers in Endocrinology, 2022)
This study was the first to evaluate multiple hormonal manipulations to hepatopancreas over the ovarian development stages of the mud crab, Scylla paramamosain. A total of 1258 metabolites in 75 hepatopancreas explants from five female crabs were induced by juvenile hormone III (JH III), methyl farnesoate (MF), farnesoic acid (FA) and methoprene (Met), as identified from combined metabolomics and lipidomics (LC-MS/MS). 101 significant metabolites and 47 significant pathways were selected and compared for their comprehensive effects to ovarian maturation. While MF played an extensive role in lipid accumulation, JH III and Met shared similar effects, especially in the commonly and significantly elevated triglycerides and lysophospholipids (fold change≥2 and ≤0.5, VIP≥1). The significant upregulation of β-oxidation and key regulators in lipid degradation by FA (P≤0.05) resulted in less lipid accumulation from this treatment, with a shift toward lipid export and energy consumption, unlike the effects of MF, JH III and Met. It was possible that MF and FA played their own unique roles and acted in synergy to modulate lipid metabolism during crab ovarian maturation. Our study yielded insights into the MF-related lipid metabolism in crustacean hepatopancreas for the overall regulation of ovarian maturation, and harbored the potential use of juvenoids to induce reproductive maturity of this economic crab species.